A STUDY ON CONSUMER BUYING BEHAVIOUR TOWARDS READY TO EAT FOODS - Barad, Manisha M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
All our business basically depends on Consumers. That is why he is considered to be the centre around which the market revolves. The lifestyle of consumers has greatly changed, speciallythe food habits. This change has given space to a new arena of Food namely- Ready to Eat Foods. It has become very popular due to advertising. Also, it is super time saving and easyto cook. Even beginners can make complex dishes with ease due to Ready to Eat options. It is available at almost every store. People are very much aware of this concept and they have accepted this style of food or cooking.